Trauma-Informed Schools Integrating Child Maltreatment Prevention, Detection, and Intervention - Panlilio, Carlomagno C. (Child Maltreatment Solutions Network, 2019)
This book provides an interdisciplinary framework for school intervention into child and adolescent maltreatment, highlighting the unique potential for schools to identify and mitigate the long-term impacts of childhood trauma on children's educational well-being. Contributors evaluate recent efforts to incorporate trauma-informed approaches into schools, including strategic planning by administrators, staff training, prevention programming, liaising with local youth service agencies, and trauma-sensitive intervention with affected students. Among the topics discussed: • The developmental impact of trauma • The role of schools and teachers in supporting student mental health • Prevention programming to prevent child and adolescent sexual abuse • Education policies to support students with traumatic histories • Responding to childhood trauma at both macro and microsystem levels Trauma-Informed Schools: Integrating Child Maltreatment Prevention, Detection, and Intervention is a valuable resource for child maltreatment researchers, educational and school psychologists, school social workers, students in early childhood and K-12 education, and education policy makers at all levels of government. It offers the necessary guidelines and insights to facilitate better learning for students who have experienced trauma, aiming to improve student well-being both inside and outside the classroom. .